Cutaneous Fusariosis in a Patient with Job’s (Hyper-IgE) Syndrome - Ahmed M. Altibi; Radhika Sheth; Ayman Battisha; Vivek Kak (Case Reports in Infectious Diseases)
Fusarium is a filamentous fungus that is ubiquitous in nature and can cause severe opportunistic infections in immunocompromised hosts. The association between Fusarium and hyper-IgE syndrome is exceedingly rare and has only been documented in a single report previously. A 44-year-old male, working as marijuana grower, with prior diagnosis of hyper-IgE syndrome and recurrent infections presented with enlarging right knee ulcer that did not respond to antimicrobial treatment. The patient was diagnosed with cutaneous fusariosis, confirmed with punch biopsy and positive wound cultures. The patient was managed with extended antifungal therapy (i.e., posaconazole) and surgical debridement resulting in remarkable improvement with wound healing leaving a pale scar. Fusarium should be considered in differential for cutaneous and invasive fungal infections in presence of cutaneous manifestations. Exposure to Cannabis plants is a noticeable risk factor. Multimodal approach involving systemic antifungals and wound debridement is essential for favorable outcome. Posaconazole was demonstrated to be a highly efficacious antifungal choice.